Pengaruh Perubahan Iklim terhadap Eksploitasi Sumber Daya di Luar Zona Ekonomi Eksklusif (ZEE) di Kawasan Arktik dalam Perspektif Maritime Security - Yolanda Yolanda; Atika Puspita Marzaman (Port Management and Maritime Administration Journal, 2025)
The Arctic region has abundant natural resource potential, which has encouraged Arctic coastal countries to explore and exploit existing resources. However, the presence of climate change has changed territorial boundaries including the Exclusive Economic Zone (EEZ) and opened up effective routes in the Arctic. Therefore, this study discusses climate change on the exploitation of resources outside the Exclusive Economic Zone by each country in the Arctic region and the impact of such exploitation on the maritime security of the Arctic sea. The approach used is qualitative-descriptive with a literature study method. The data used are secondary data obtained from books, journal articles, and relevant and trusted websites. The theories used in this study are climate change/climate change and maritime security/maritime security. The results of this study indicate that there is an influence of climate change on the opening of access and rising sea levels in the Arctic which results in uncertain territorial sea boundaries. Thus encouraging exploitation in the Arctic region which has implications for maritime security.